A Conceptual Framework of Customer Behavior in Software Public Training: Integrating TAM, TPB, and Sustainable Marketing in Vocational Higher Education - Fajar, Lestari; Usep, Suhud; Setyo Ferry, Wibowo; Christian Wiradendi, Wolor (INTI International University, 2026)
This conceptual paper presents an integrated framework to analyze customer behavior in Software Public Training (SPT) within vocational higher education in West Java, addressing a critical gap in understanding the adoption dynamics among external customer. As vocational institutions increasingly deploy software-based training to meet industry demands for digital competencies, this paper synthesizes three leading theoretical models Technology Acceptance Model (TAM), Theory of Planned Behavior (TPB), and Sustainable Marketing to propose a unified approach to predicting training adoption. Advancing beyond existing empirical models, the framework introduces perceived convenience, value, service quality, and subjective demonstration as key antecedents of trust and attitude, which in turn drive purchase intention. By embedding long-term ethical value creation into the TAM-TPB paradigm, this study offers a novel state-of-the-art perspective that aligns usability, social influence, and sustainability within training design. The resulting model not only enriches theoretical discourse but also provides vocational institutions with a future-ready strategy for designing effective, customer-centered, and ethically grounded training services.